The viability and potential of environmental DNA (eDNA) detection of freshwater fish based on current genetic resources in Malaysia - Kaviarasu Munian; Farah Farhana Ramli; Nursyuhada Othman; Hidayah Haris; Nur Hartini Sariyati; Nur Aina Amira Mahyudin; Mohd Faudzir Najmuddin; Mohd Shahfiz Azman; Muhammad Abu Bakar Abdul-Latiff (Penerbit Universiti Kebangsaan Malaysia, 2024)
Environmental DNA (eDNA) metabarcoding is a promising tool for regular biological monitoring, especially for freshwater fish, which are facing tremendous threats worldwide. The application of eDNA detection is a dramatic improvement on common methods of biomonitoring as it produces tangible results in a short time with low effort and little expense. However, the accuracy of the technique is largely dependent on the availability of genetic references for the target organisms. In this study, we investigated the availability of genetic resources for freshwater fish in Malaysia in three public depositories, National Center for Biotechnology Information (NCBI), Barcode of Life Data System (BOLD), and Mitochondrial Genome Database of Fish (MitoFish), focusing on seven targeted genes of mitochondrial DNA. We found that only 68.6% of freshwater fish found in Malaysia had information on at least one of the seven targeted genes, with data on Cytochrome C Oxidase Subunit I being most commonly available. Genetic information for threatened and endemic species were underrepresented (33.3%-41.7%), yet fish of commercial value and invasive species were well explored genetically. Although there is still room for improvement to achieve comprehensive and reliable genetic resource information for freshwater fish in Malaysia, the application of eDNA metabarcoding is still highly relevant. This is since the current decline in freshwater fish diversity in Malaysia is alarming and because the technique will assist in the ongoing effort to generate new genetic references for Malaysian freshwater fish.